Gerakan #dirumahaja sebagai Aktivisme Digital pada Akun Media Sosial Najwa Shihab - Chusna, Aidatul (KAMBOTI: Jurnal Sosial dan Humaniora, 2021)
This paper discusses how the #dirumahaja movement initiated by Najwa Shihab in her various social media accounts becomes a form of digital activism in a network society. With a qualitative descriptive method, this study will look at how the phenomenon of the #dirumahaja movement is carried out and the extent of the impact of this digital activism. Therefore, posts in the form of information or videos uploaded to Najwa Shihab's social media accounts are the primary data in this analysis. The result of the discussion shows that through various social media platforms that she holds, Najwa Shihab carried out various forms of campaigns that invite people to do activities at home in various forms, such as sharing informative videos about the dangers of covid-19 and the importance of reducing activities outside the home and inviting public figures in various video content, as well as organizing charity music concerts.